Machine Learning based Signal Generation Strategies for High-Speed Optical Transmitters - Rossi, Andrea (2022)
Optical communication is the only viable solution to respond to the demand for a high bit rate and long transmission distance. Directly modulated lasers (DMLs) are a cheap solution for modulating the light in optical fibre. Moreover, their hardware is simpler than externally modulated lasers. However, DML is inherently chirped and the transmission length with high bit rate is limited. This work explores and implements neural networks based signal predistortion schemes to create transmitters. open